2015
DOI: 10.3945/jn.114.201293
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intakes of Glutamic Acid and Glycine Are Associated with Stroke Mortality in Japanese Adults ,

Abstract: The data suggest that glutamic acid and glycine intakes may be associated with risk of stroke mortality. Given that this is an initial observation, our results need to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Dietary glycine and methionine that are mainly consumed from animal-based foods have been shown to be positively associated with T2D, hypertension, and stroke mortality in previous cohort studies (36)(37)(38). The dietary amino acid composition may partly explain the association between animal protein intake and the development of T2D.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Dietary glycine and methionine that are mainly consumed from animal-based foods have been shown to be positively associated with T2D, hypertension, and stroke mortality in previous cohort studies (36)(37)(38). The dietary amino acid composition may partly explain the association between animal protein intake and the development of T2D.…”
Section: Discussionmentioning
confidence: 92%
“…The potential benefits of high intake of plant protein in the prevention of T2D might also be related to the amino acid composition. Dietary glutamic acid, which is an amino acid that is mainly consumed from plant protein, is inversely associated with risks of hypertension, arterial stiffness, and stroke mortality (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The present study included 29,079 subjects with no history of cancer, stroke, or coronary heart disease. The details of the study design and subjects have been described previously (14,15).…”
Section: Methodsmentioning
confidence: 99%
“…Diet including alcohol intake was assessed with a 169-item semiquantitative FFQ at the baseline. Details of the method of calculating nutrient intakes from the FFQ and its reliability and validity were previously described (15,16). Nutrient values in foods including folate and B vitamins were obtained from the Japanese Standard Tables of Food Composition, 5th revised and enlarged edition, published by the Science and Technology Agency of Japan (17).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between the types of dietary protein intake and cardiovascular disease (CVD) also remains unclear. Some epidemiological studies have shown no association between any kind of protein intake and CVD [16][17][18][19] , whereas other studies reported inverse associations between animal protein intake and intracerebral hemorrhage 20,21) or any type of protein and risk of cerebral infarction 22) . However, to our knowledge only a few reports have suggested an inverse association between vegetable protein intake and risk of CVD 23) .…”
Section: Dietary Surveymentioning
confidence: 99%